Comparative Analysis of Forced Defence (Noodweer) in Dealing with the Crime of Persecution: A Study of Indonesian Criminal Law and Islamic - Sitti Ma'rifah Nisrina; Haerana Haerana; Nur Azisa (Khazanah Hukum, 2023)
This research delves into the legal framework of forced Defence in addressing the crime of persecution, examining its application in Indonesian criminal law and its comparison with Islamic law. The study employs a normative legal approach, utilizing statutory analysis and case study methods to provide insights into the nuanced distinctions between the two legal systems. The investigation reveals that forced defence arrangements are rooted in juridical considerations, which evaluate the circumstances of victims and perpetrators according to the principles and conditions delineated in the Criminal Code. Intent, legal psychology, and human instincts for self-preservation are integral to the evaluation process. Positive and Islamic laws allow forced Defence when actions align with expert opinions and scholarly interpretations. However, Islamic criminal law limits Defence , prohibiting actions that lead to death or adultery. This study contributes to understanding the legal rationale underpinning forced Defence Â in the context of persecution. It underscores the similarities and disparities between Indonesian criminal law and Islamic law.